Magic Mountains and Multi-disciplines in International Medical Mobilities; Comment on "Patient Mobility in the Global Marketplace: A Multidisciplinary Perspective" - Tomas Mainil; Herman Meulemans (Kerman University of Medical Sciences, 2014)
Medical mobilities offer both opportunities and challenges. This tension follows the same ratio as many other historic fora, but offers at the same time a sustainable equilibrium. Multi-disciplines are, therefore, the key to the medical lifeworld for the global health and well-being of transnational health users around the globe.